The environmental history of the oxbow in the Luciąża River valley – Study on the specific microclimate during Allerød and Younger Dryas in central Poland. (20th January 2023) - Antczak-Orlewska, Olga; Okupny, Daniel; Pawłowski, Dominik; Kotrys, Bartosz; Krąpiec, Marek; Luoto, Tomi P.; Peyron, Odile; Płóciennik, Mateusz; Stachowicz-Rybka, Renata; Wacnik, Agnieszka; Szmańda, Jacek B.; Szychowska-Krąpiec, Elżbieta; et al.
Abstract: The vicinity of the Rozprza archaeological site (central Poland) has been the area of a series of palaeoecological studies tracking the environmental history of the Luciąża River valley up to ca. 13, 200 cal. BP. Numerous subfossil palaeomeanders of different sizes have been discovered in the valley floor. Here, we present the first results of multiproxy research on the paleo-oxbow lake fill, one of the oldest in the region. The wide range of palaeoecological analyses resulted in reconstructions of vegetation history, climatic, hydrological and habitat changes. The studied oxbow was an aquatic ecosystem with diverse invertebrate fauna until the end of Younger Dryas when it transformed into a limno-telmatic habitat. The sediment composition indicates active denudation processes and several episodes of turbulent hydrological conditions. Such an increased river activity could have caused flooding, resulting in an allochthonous matter supply to the oxbow lake in Late Vistulian. Environmental changes were strictly related to the regional features of the catchment, the transformation of soils, and the hydrogeological conditions. The chironomid- and pollen-inferred climatic reconstructions indicate periods of high and low continentality. The chironomid record indicates relatively cool summer conditions in the Allerød, especially ca. 13, 000 cal. BP, possibly related to the Gerzensee Oscillation. On the other hand, a distinct increase of summer temperatures in Younger Dryas (up to 16 °C) was recorded. Such a situation was also confirmed in some other studies from the region, suggesting that it might be the effect of some specific, local palaeoclimatic conditions.